A little dinner for Lincoln - Storm, Colton, 1908-
Typescript article describing the dinner held before the opening of the Robert Todd Lincoln collection of Abraham Lincoln papers at the Library of Congress, July 1, 1947, and a published version of same.
Author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Anniversaries, etc; Lincoln, Abraham, -- 1809-1865 -- Archival resources; Lincoln, Robert Todd, -- 1843-1926.; Library of Congress -- Anniversaries, etc; Authors